Seed Predation by Rodents and Implications for Plant Recruitment in Defaunated Atlantic Forests - Galetti, Mauro [UNESP]; Guevara, Roger; Galbiati, Lígia A. [UNESP]; Neves, Carolina L. [UNESP]; Rodarte, Raisa R. [UNESP]; Mendes, Calebe P. [UNESP] (Wiley, 2015)
Rodents are known to perform post-dispersal seed predation in tropical rain forest, but there is little information on the identity of these seed predators and how they select their seeds. Using cafeteria experiments, we found that seed mass, rodent body mass, and the ratio of seed/rodent mass were determinants of seed consumption.
Keywords: Allometric relationship; Atlantic forest; Defaunation; Forest regeneration; Post-dispersal predation; Seed size